2022
DOI: 10.3897/bdj.10.e79923
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and vertical distribution patterns of wildlife in Tianzhushan, Shaanxi Province, China

Abstract: Biodiversity monitoring is an important means by which to evaluate management effectiveness and develop sound conservation plans. In this study, 52 cameras were installed in the study area of Tianzhushan to assess wildlife diversity and elevational patterns from 2018 to 2019. In total, 9 541 independent photos were collected within 26 565 camera-days. We analysed the relative abundance index (RAI), activity patterns and seasonal activity rhythms of the five most abundant species at 200-m elevational intervals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was also worth noting that there was a separation of peak activity times for both in the cold season. On the one hand, it suggested that these ungulates increase their activity duration (e.g., exhibiting two activity peaks) during favourable periods (such as daylight hours) in the warm season to increase foraging efficiency and store sufficient fat reserves for potential food shortages in the cold season 62 , 63 . On the other hand, the staggered activity peak of the two and lower overlap coefficients in the cold season also suggested that ungulates may coexist with competing species through temporal ecological niche partitioning in the resource-poor cold season 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also worth noting that there was a separation of peak activity times for both in the cold season. On the one hand, it suggested that these ungulates increase their activity duration (e.g., exhibiting two activity peaks) during favourable periods (such as daylight hours) in the warm season to increase foraging efficiency and store sufficient fat reserves for potential food shortages in the cold season 62 , 63 . On the other hand, the staggered activity peak of the two and lower overlap coefficients in the cold season also suggested that ungulates may coexist with competing species through temporal ecological niche partitioning in the resource-poor cold season 46 .…”
Section: Discussionmentioning
confidence: 99%